2006
DOI: 10.1002/cncr.21922
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and extent of disease multigene assay for malignant thyroid neoplasms

Abstract: Objective Intracranial arterial dolichoectasia (IADE), also called dilatative arteriopathy of the brain, is defined as an increase in length and diameter of intracranial arteries. Abdominal aortic aneurysm and ectasia of coronary arteries have been reported in association with IADE. In both conditions, a dysfunction of matrix metalloproteinases (MMP)‐2, ‐3, and ‐9 have been found. Our aim was to investigate these MMP pathways in stroke patients with IADE. Methods Five hundred ten Caucasians patients with brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
42
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 57 publications
3
42
0
Order By: Relevance
“…Therefore, mutation analysis alone is insufficient to classify most malignant indeterminate lesions on FNA. Several reports have identified gene panels ranging from 6 to 105 genes with high sensitivity and specificity at differentiating benign from malignant thyroid tissue samples (31)(32)(33)(34)(35)(36). Although these findings are encouraging, the predictive accuracy of these gene panels in FNA samples in a real-world setting remains limited, as these were validated on small cohorts of patients and did not analyze samples with indeterminate cytology on FNA.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, mutation analysis alone is insufficient to classify most malignant indeterminate lesions on FNA. Several reports have identified gene panels ranging from 6 to 105 genes with high sensitivity and specificity at differentiating benign from malignant thyroid tissue samples (31)(32)(33)(34)(35)(36). Although these findings are encouraging, the predictive accuracy of these gene panels in FNA samples in a real-world setting remains limited, as these were validated on small cohorts of patients and did not analyze samples with indeterminate cytology on FNA.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, higher expression of TMPRSS4 was associated with positive lymph node metastasis, larger tumor size, advanced pathological grade, and shorter overall and disease-free survival; 16 in non-small cell lung cancer, overexpression of TMPRSS4 in patients with squamous histology was associated with poor prognosis; 24 in malignant thyroid neoplasm, TMPRSS4 was identified to be a diagnostic marker. 25 Of note, Jung et al had reported TMPRSS4 was upregulated in colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TMPRSS4, which was initially termed TMPRSS3, was identified as a protein up-regulated in pancreatic cancer (24). It is also up-regulated in gastric, colon, and thyroid cancers (24,36), suggesting that TMPRSS4 may have a role in tumor progression. In fact, recent study has revealed that overexpression of TMPRSS4 in colon cancer cells enhances invasiveness and induces EMT (20), findings that are in accord with our present observations.…”
Section: Discussionmentioning
confidence: 99%